2-year outcomes of ranibizumab versus laser therapy for the treatment of very low birthweight infants with retinopathy of prematurity (RAINBOW extension study): prospective follow-up of an open label, randomised controlled trial - Marlow, Neil; Stahl, Andreas; Lepore, Domenico; Fielder, Alistair; Reynolds, James D; Zhu, Qi; Weisberger, Annemarie; Stiehl, Daniel P; Fleck, Brian (The lancet child & adolescent health, 2021)
Intravitreal injection of vascular endothelial growth factor (VEGF) inhibitors is increasingly used to treat retinopathy of prematurity (ROP) in the absence of evidence about long-term efficacy or safety. In this prespecified interim analysis of the RAINBOW extension study, we aimed to prospectively assess outcomes at age 2 years.BACKGROUNDIntravitreal injection of vascular endothelial growth factor (VEGF) inhibitors is increasingly used to treat retinopathy of prematurity (ROP) in the absence of evidence about long-term efficacy or safety. In this prespecified interim analysis of the RAINBOW extension study, we aimed to prospectively assess outcomes at age 2 years.RAINBOW was an open-label, randomised trial that compared intravitreal ranibizumab (at 0·1 mg and 0·2 mg doses) with laser therapy for the treatment of ROP in very low birthweight infants (<1500 g). Families of the 201 infants that completed the RAINBOW core study were approached for consent to enter the extension study, which evaluates treatment outcomes prospectively through to 5 years of age. At age 20-28 months corrected for prematurity, participants had ophthalmic, development, and health assessments. The primary outcome was the absence of structural ocular abnormalities; secondary outcomes included vision-related quality of life (reported by parents using the Children's Visual Function Questionnaire), development (assessed with the Mullen Scales of Early Learning), motor function, and health status. Investigator-determined ocular and non-ocular serious and other adverse events were recorded. This study is registered with ClinicalTrials.gov, NCT02640664.METHODSRAINBOW was an open-label, randomised trial that compared intravitreal ranibizumab (at 0·1 mg and 0·2 mg doses) with laser therapy for the treatment of ROP in very low birthweight infants (<1500 g). Families of the 201 infants that completed the RAINBOW core study were approached for consent to enter the extension study, which evaluates treatment outcomes prospectively through to 5 years of age. At age 20-28 months corrected for prematurity, participants had ophthalmic, development, and health assessments. The primary outcome was the absence of structural ocular abnormalities; secondary outcomes included vision-related quality of life (reported by parents using the Children's Visual Function Questionnaire), development (assessed with the Mullen Scales of Early Learning), motor function, and health status. Investigator-determined ocular and non-ocular serious and other adverse events were recorded. This study is registered with ClinicalTrials.gov, NCT02640664.Between June 16, 2016, and Jan 22, 2018, 180 infants were enrolled in the RAINBOW extension study, and 153 (85%) were evaluated at 20-28 months of age. No child developed new ocular structural abnormalities. Structural abnormalities were present in one (2%) of 56 infants in the ranibizumab 0·2 mg group, one (2%) of 51 infants in the 0·1 mg group, and four (9%) of 44 infants in the laser therapy group. The odds ratio of no structural abnormality was 5·68 (95% CI 0·60-54·0; p=0·10) for ranibizumab 0·2 mg versus laser therapy, 4·82 (0·52-45·0; p=0·14) for ranibizumab 0·1 mg versus laser therapy, and 1·21 (0·07-20; p=0·90) for ranibizumab 0·2 mg vs 0·1 mg. High myopia (-5 dioptres or worse) was less frequent after 0·2 mg ranibizumab (five [5%] of 110 eyes) than with laser therapy (16 [20%] of 82; odds ratio 0·19, 95% CI 0·05-0·69; p=0·012). Composite vision-related quality of life scores seemed higher among the ranibizumab 0·2 mg group (mean 84, 95% CI 80-88) compared with laser therapy (77, 72-83; p=0·063). Mullen Scales T-scores for visual reception, receptive and expressive language were distributed similarly between the three trial groups and there were similar proportions of infants with motor and hearing problems among treatment groups. The proportion of infants with respiratory symptoms and Z scores of standing height, weight, and head circumference were similarly distributed in the treatment groups. There were no adverse events considered by the investigator to be related to the study intervention.FINDINGSBetween June 16, 2016, and Jan 22, 2018, 180 infants were enrolled in the RAINBOW extension study, and 153 (85%) were evaluated at 20-28 months of age. No child developed new ocular structural abnormalities. Structural abnormalities were present in one (2%) of 56 infants in the ranibizumab 0·2 mg group, one (2%) of 51 infants in the 0·1 mg group, and four (9%) of 44 infants in the laser therapy group. The odds ratio of no structural abnormality was 5·68 (95% CI 0·60-54·0; p=0·10) for ranibizumab 0·2 mg versus laser therapy, 4·82 (0·52-45·0; p=0·14) for ranibizumab 0·1 mg versus laser therapy, and 1·21 (0·07-20; p=0·90) for ranibizumab 0·2 mg vs 0·1 mg. High myopia (-5 dioptres or worse) was less frequent after 0·2 mg ranibizumab (five [5%] of 110 eyes) than with laser therapy (16 [20%] of 82; odds ratio 0·19, 95% CI 0·05-0·69; p=0·012). Composite vision-related quality of life scores seemed higher among the ranibizumab 0·2 mg group (mean 84, 95% CI 80-88) compared with laser therapy (77, 72-83; p=0·063). Mullen Scales T-scores for visual reception, receptive and expressive language were distributed similarly between the three trial groups and there were similar proportions of infants with motor and hearing problems among treatment groups. The proportion of infants with respiratory symptoms and Z scores of standing height, weight, and head circumference were similarly distributed in the treatment groups. There were no adverse events considered by the investigator to be related to the study intervention.2-year outcomes following ranibizumab 0·2 mg for the treatment of ROP confirm the ocular outcomes of the original RAINBOW trial and show reduced high myopia, with possibly better vision-related quality of life. This treatment did not appear to affect non-ocular infant development.INTERPRETATION2-year outcomes following ranibizumab 0·2 mg for the treatment of ROP confirm the ocular outcomes of the original RAINBOW trial and show reduced high myopia, with possibly better vision-related quality of life. This treatment did not appear to affect non-ocular infant development.Novartis Pharma AG.FUNDINGNovartis Pharma AG.